Mukhabarah-Based Productive Waqf Development Strategy In Improving Community Welfare In Bireuen - Mulyana Fitri; Marliyah Marliyah; Muhammad Arif (LPPM Universitas PGRI Sumatera Barat, 2024)
This research aims to find out what strategies are currently being implemented to develop mukhabarah-based productive waqf in improving the welfare of the people in Bireuen and most importantly to determine the main priority strategy in developing mukhabarah-based productive waqf in improving the welfare of the people in Bireuen. The methods used are SWOT analysis and QSPM. The number of respondents was 6 people and 5 people respectively. Respondents were appointed based on their understanding of waqf, especially regarding the development of productive waqf, both from academics and practitioners. For the SWOT analysis research results, the strategy quadrant after processing the IFAS and EFAS matrix values is a progressive strategy (moving forward). This strategy means that it is necessary to take advantage of existing strengths and opportunities to form a new strategy in developing mukhabarah-based productive waqf. Its strength lies in the principle of productive waqf itself which carries a mukhabarah agreement (agricultural profit sharing), because this can help welfare and increase people's income. The opportunity can be seen from the increase in people's income from the results of waqf rice fields and good economic development which provides opportunities for productive waqf management. And public awareness about waqf continues to increase, especially since this is in line with the public's desire to give waqf. Thus, the main priority strategy that needs to be implemented in the development of mukhabarah-based productive waqf is increasing farmers' income from the results of mukhabarah rice field waqf, by providing training and guidance to farmers to improve agricultural techniques, use of fertilizer, soil management, and selection of superior seeds. increase crop yields significantly.